2020
DOI: 10.3390/ijgi9100596
|View full text |Cite
|
Sign up to set email alerts
|

A Smooth Transition Algorithm for Adjacent Panoramic Viewpoints Using Matched Delaunay Triangular Patches

Abstract: The unnatural panoramic image transition between two adjacent viewpoints reduces the immersion and interactive experiences of 360° panoramic walkthrough systems. In this paper, a dynamic panoramic image rendering and smooth transition algorithm for adjacent viewpoints is proposed. First, the feature points of adjacent view images are extracted, a robust matching algorithm is used to establish adjacent point pairs, and the matching triangles are formed by using the homonymous points. Then, a dynamic transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is observed that image completion methods often lead to deformations in local rigid structures during the rectification process. Moreover, when addressing the boundaries of missing regions, noticeable boundary effects are common, as image completion methods need to ensure smooth transitions between the filled area and the surrounding region, leading to prominent boundary artifacts [55][56][57]. In addition, this article also presents other qualitative comparison results, as shown in Appendix A Figures A1 and A2.…”
Section: Qualitative Comparison Of Image Rectificationmentioning
confidence: 99%
“…It is observed that image completion methods often lead to deformations in local rigid structures during the rectification process. Moreover, when addressing the boundaries of missing regions, noticeable boundary effects are common, as image completion methods need to ensure smooth transitions between the filled area and the surrounding region, leading to prominent boundary artifacts [55][56][57]. In addition, this article also presents other qualitative comparison results, as shown in Appendix A Figures A1 and A2.…”
Section: Qualitative Comparison Of Image Rectificationmentioning
confidence: 99%
“…It is observed that image completion methods often lead to deformations in local rigid structures during the rectification process. Moreover, when addressing the boundaries of missing regions, noticeable boundary effects are common, as image completion methods need to ensure smooth transitions between the filled area and the surrounding region, leading to prominent boundary artifacts [55][56][57]. In addition, this article also presents other qualitative comparison results, as shown in Appendix A Figures A1 and A2.…”
Section: Qualitative Comparison Of Image Rectificationmentioning
confidence: 99%
“…In recent years, the construction of projects such as “National 3D Real Scene” (Zhang, Huang, et al, 2021) and “Digital Twin” (Gu et al, 2020) has been gradually promoted throughout the country, and the representation of spatiotemporal objects in the real world has also been reformed and upgraded from a 2D plane to a 3D scene (Liu, 2019; Yu et al, 2021; Zhao et al, 2020). 3D real scene is a digital virtual space that represents and portrays the real world in a photorealistic, three‐dimensional, and sequential manner.…”
Section: Introductionmentioning
confidence: 99%